IgG1 and IgG4 antibody responses to the Anopheles gambiae salivary protein gSG6 in the sympatric ethnic groups Mossi and Fulani in a malaria hyperhendemic area of Burkina Faso. - Cinzia Rizzo; Raffaele Ronca; Fabrizio Lombardo; Valentina Mangano; Sodiomon Bienvenu Sirima; Issa Nèbiè; Gabriella Fiorentino; Marita Troye-Blomberg; David Modiano; Bruno Arcà (PLoS ONE)
Human antibody response to the Anopheles gambiae salivary protein gSG6 has recently emerged as a potentially useful tool for malaria epidemiological studies and for the evaluation of vector control interventions. However, the current understanding of the host immune response to mosquito salivary proteins and of the possible crosstalk with early response to Plasmodium parasites is still very limited. We report here the analysis of IgG1 and IgG4 subclasses among anti-gSG6 IgG responders belonging to Mossi and Fulani from Burkina Faso, two ethnic groups which are known for their differential humoral response to parasite antigens and for their different susceptibility to malaria. The IgG1 antibody response against the gSG6 protein was comparable in the two groups. On the contrary, IgG4 titers were significantly higher in the Fulani where, in addition, anti-gSG6 IgG4 antibodies appeared in younger children and the ratio IgG4/IgG1 stayed relatively stable throughout adulthood. Both gSG6-specific IgG1 and IgG4 antibodies showed a tendency to decrease with age whereas, as expected, the IgG response to the Plasmodium circumsporozoite protein (CSP) exhibited an opposite trend in the same individuals. These observations are in line with the idea that the An. gambiae gSG6 salivary protein induces immune tolerance, especially after intense and prolonged exposure as is the case for the area under study, suggesting that gSG6 may trigger in exposed individuals a Th2-oriented immune response.